2011
DOI: 10.14411/fp.2011.011
|View full text |Cite
|
Sign up to set email alerts
|

A redescription of Arostrilepis horrida (Linstow, 1901) and descriptions of two new species from Palaearctic microtine rodents, Arostrilepis macrocirrosa sp. n. and A. tenuicirrosa sp. n. (Cestoda: Hymenolepididae)

Abstract: the type species of the cestode genus Arostrilepis Mas-coma et tenora, 1997, Arostrilepis horrida (linstow, 1901), is redescribed on the basis of the syntype material from the brown rat (Rattus norvegicus) deposited in the collection of the Museum für Naturkunde, Berlin. Arostrilepis horrida (sensu lato), reported from a wide range of rodents throughout the Holarctic region, is shown to be a species complex. the proposed host range and geographical distribution of A. horrida (sensu stricto) are limited to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…comparative studies by rausch (1952), schiller (1952), Voge (1952), Murai and tenora (1973), Egorova and Nadtochii (1975) and others failed to recognize species limits based on structural characters (some reasons for this are outlined in Hoberg et al 2003). A re-examination of the type series revealed that data for host range and geographical distribution of A. horrida (sensu stricto) are limited to those reported in the original description (Makarikov et al 2011). consequently, there are still unresolved questions regarding this species (i.e., morphology of gravid proglottides and validity of the type host).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…comparative studies by rausch (1952), schiller (1952), Voge (1952), Murai and tenora (1973), Egorova and Nadtochii (1975) and others failed to recognize species limits based on structural characters (some reasons for this are outlined in Hoberg et al 2003). A re-examination of the type series revealed that data for host range and geographical distribution of A. horrida (sensu stricto) are limited to those reported in the original description (Makarikov et al 2011). consequently, there are still unresolved questions regarding this species (i.e., morphology of gravid proglottides and validity of the type host).…”
mentioning
confidence: 99%
“…Previous studies have suggested that the type species of the genus Arostrilepis Mas-coma et tenora, 1997, A. horrida (linstow, 1901), which has a presumed Holarctic distribution, represents a complex of cryptic species (Johri 1956, Mas-coma et al 1980, Kontrimavichus and smirnova 1991, gulyaev and chechulin 1997, Mascoma and tenora 1997, Asakawa et al 2002, Hoberg et al 2003, cook et al 2005, Hwang et al 2007, Haukisalmi et al 2009, 2010, Makarikov et al 2011. But for most of the last century, A. horrida was considered to represent a single, widespread (geographically and with respect to microtine hosts), and hyper-variable species.…”
mentioning
confidence: 99%
See 3 more Smart Citations